Detection of the Ancient Rivers in the Western Part of Basra Governorate by Using Remote Allergies - Lazim Lafta, Researcher. Mohamed; Khalid Al-Ali , Assist Prof. Ali (Basra studies journal, 2025)
Southern Iraq's Al-Zubair area encounters geological obstacles when it comes to researching and comprehending ancient rivers and their impact on the creation of the ancient city of Basra (Al-Zubair currently). This includes significant locations like Safwan, Umm Qasr, Khor Al-Zubair, and Al-Burjisiya.The study aims to discover and comprehend ancient water sources in the area and how they influenced the region's natural and cultural evolution over time. Through the utilization of remote sensing methods with satellite imagery, ancient rivers in the research area are identified.Satellites like LandSat, managed by NASA, were utilized. Capturing detailed satellite images of the surface landscape with the Landsat 8 satellite. The images underwent processing and analysis using the ArcGIS software, known as a dominant tool for extracting precise geological data from aerial and satellite images.Satellite images and historical sources have confirmed the existence of ancient rivers like the Euphrates and Abu Al-Khasib in the Khor Al-Zubair river branches area.Around 3,750 years ago, tectonic activity in the Khor Al-Zubair area caused significant changes in land formation and altered the path of the Euphrates River. It is believed by scientists that it also impacted the Abu Al-Khasib River, causing Khor Al-Zubair to change from an estuary into a linear lake.The research demonstrated the existence of the historic Euphrates River and the ancient Abu Al-Khasib River in the area, along with various other watercourses. These discoveries improve our comprehension of historical sources and accounts of ancient Basra flooding due to water sourced from.